Regulation of centromeric histone localization in budding yeast - Hildebrand, Erica (My University, 2017)
The exclusive localization of the histone H3 variant CENP-A to centromeres is essential for accurate chromosome segregation. Ubiquitin-mediated proteolysis helps to ensure that CENP-A does not mislocalize to euchromatin, which can lead to genomic instability. Consistent with this, overexpression of budding yeast CENP-ACse4 is lethal in cells lacking Psh1, the E3 ubiquitin ligase that targets CENP-ACse4 for degradation. To identify additional mechanisms that prevent CENP-ACse4 misincorporation and lethality, I analyzed the genome-wide mislocalization pattern of overexpressed CENP-ACse4 in the presence and absence of Psh1 by chromatin immunoprecipitation followed by high throughput sequencing. I found that ectopic CENP-ACse4 is enriched at promoters that contain histone H2A.ZHtz1 nucleosomes, but that H2A.ZHtz1 is not required for CENP-ACse4 mislocalization. Instead, INO80-C, which removes H2A.ZHtz1 from nucleosomes, promotes the ectopic deposition of CENP-ACse4. Transcriptional profiling revealed gene expression changes in the psh1∆ cells overexpressing CENP-ACse4. The down-regulated genes are enriched for CENP-ACse4 mislocalization to promoters, while the up-regulated genes correlate with those that are also transcriptionally upregulated in an htz1∆ strain. Together, these data show that regulating centromeric nucleosome localization is not only critical for maintaining centromere function, but also for ensuring accurate promoter function and transcriptional regulation. To determine whether there are features of the CENP-ACse4 nucleosome that facilitate Psh1-mediated proteolysis, a genetic screen was performed to identify histone H4 residues that regulate CENP-ACse4 degradation. H4-R36 is a key residue identified from this screen that promotes the interaction between CENP-ACse4 and Psh1. Consistent with this, CENP-ACse4 protein levels are stabilized in H4-R36A mutant cells and CENP-ACse4 is enriched in the euchromatin. The defects in CENP-ACse4 proteolysis may be related to changes in Psh1 localization, as Psh1 becomes enriched at 3’ intergenic regions in H4-R36A mutant cells. These data reveal a key residue in histone H4 that is important for efficient CENP-ACse4 degradation, likely by facilitating the interaction between Psh1 and CENP-ACse4. My work reveals details of the Psh1 regulated mislocalization pathway for CENP-ACse4 in budding yeast. As CENP-A is mislocalized in some cancer cells, it is important to understand the regulatory mechanisms involved with controlling centromeric histone mislocalization. Future work will determine if any of the mechanisms identified here are conserved in other organisms, or if they are perturbed during oncogenesis.
Thesis (Ph.D.)--University of Washington, 2016-12
Keywords: Centromere; Chromatin; Cse4; Histone; Psh1; Ubiquitin; Molecular biology; Genetics; Biochemistry; molecular and cellular biology